The effect of team formation on defensive performance in Australian football. Issue 2 (February 2022) - Aarons, Mitchell F.; Young, Christopher M.; Bruce, Lyndell; Dwyer, Dan B.
Abstract: Objectives: Understanding the successful characteristics of team formation during different scenarios in Australian Football matches can assist coaches in making important tactical match-day and training decisions. The aims of this study were to explore the outcomes of entries inside 50 m of the goal, in Australian Football and to determine whether there was an association between team formation and team defensive performance after a turnover. Design: Observational. Methods: Global Positioning System (GPS) data, technical event data and video files from 22 matches in one season were obtained from an elite Australian Football club. Of 1092 forward 50 entries, 392 possession chains that resulted in a turnover were analysed. Variables representing team formation of players at the occurrence of turnover were compared between positive and negative outcomes of the subsequent possession chain. Logistic regression and decision tree modelling were also used to explore associations and variable importance. Results: None of 18 team formation characteristics differed between positive and negative outcomes of turnovers. Multivariate modelling identified that having a team formation with greater width than length made it more likely to result in a positive outcome (Decision tree classification accuracy = 69.5%, AUROC = 0.72). Conclusions: No single characteristic of team formation affects the outcome of a turnover possession chain, however team formation that was wider than it was long may be associated with a more desirable outcome. The lack of association between most team formation characteristics and defensive outcomes, highlight the risk of over emphasising team formation in tactical planning for some phases of play.